An alliance between Cyprus and Greece: Assessing its partners' relative security contribution - Vrahatis, M. N.; Parsopoulos, K. E.; Andreou, Andreas S.; Zombanakis, G. A. (My University, 2004)
The issue that this paper tackles is the assessment of the relative security benefits that Cyprus and Greece derive in the context of their cooperation on defence matters. This form of cooperation, known as the 'Integrated Defence Space Doctrine', aims at defending their interests in the Aegean Sea and the broader East Mediterranean theatre. The paper relies heavily on earlier research on this topic, which deals with the Greek-Cypriot alliance facing an arms race against Turkey, and uses a coefficient especially designed to assess the optimal levels of security and the associated defence expenditure of the two allies. A comparison of the relative security coefficient values for the two allies suggests that the security benefit that Greece derives thanks to its alliance with Cyprus exceeds the corresponding Cypriot benefit by far. Given the importance assigned to human resources by this index, in conjunction with the demographic problems of Greece, this conclusion justifies the recent Greek defence policy revision, emphasizing quality, capital equipment and flexibility of forces. This revision aims at satisfying the security requirements of the alliance and the increasing demands of an arms race against Turkey.
Keywords: Relative military security; Arms race; Defence expenditure; Optimal control